Cryptocurrency and crowdfunding / Amirah Elyana Shamsuddin … [et al.] - Shamsuddin, Amirah Elyana; Yusri, Atikah Nabilah; Abdul Moin, Nur Asyiqin; Mohamed Shaiful Azam, Nur Fatini; Sabri, Nur Huda Syazana (2023)
In the growing era of the digital revolution, cryptocurrency and crowdfunding have impacted the financial industry as crowdfunding and cryptocurrency have emerged as the latest advancements in business and are used in financial matters. This is because cryptocurrency and crowdfunding have provided a paradigm shift in the financial world where both can generate money and profit. Cryptocurrencies use blockchain technology to introduce decentralized currencies while crowdfunding enables the collection of large amounts of funds through online community engagement. Cryptocurrency is a form of digital currency used to exchange goods and services. Cryptocurrencies have shown that they arc the future of commerce by replacing physical currencies (Ullah & Nazim, 2021). Crowd funding is an innovative way for entrepreneurs to raise funds from people for their business or community projects. In exchange for their contribution, these individuals may receive rewards or join a share in the venture (Mollick, 2014). Therefore, this study will explore and examine how cryptocurrency and crowdfunding can provide a deeper understanding of each of them and be able to understand how this financial system works. Through this study, we examine every definition of cryptocurrency and crowdfunding, current issues of cryptocurrency and crowdfunding, and fatwas related to cryptocurrency and crowdfunding.